Inflammatory activation of the FcγR and IFNγR pathways co-influences the differentiation and activity of osteoclasts - Groetsch, Bettina; Schachtschabel, Elisabeth; Tripal, Philipp; Schmid, Benjamin; Smith, Ana-Suncana; Schett, Georg; Bozec, Aline (Frontiers in Immunology, 2022)
Osteoclasts are polykaryons formed by cell-cell fusion of highly motile progenitors of the myeloid lineage. Osteoclast activity can preserve skeletal strength and bone homeostasis. However, osteoclasts are responsible for bone destruction in rheumatoid arthritis (RA). Fc receptors activated by IgG immune complexes (IC) can boost osteoclast differentiation and bone loss in the course of RA. In contrast, IFNg secreted by immune cells blocks osteoclast activation. Despite their hypothetical importance in the regulation of osteoclast differentiation in RA, the interconnection between the two pathways has not been described so far. Here, we show by total internal reflection fluorescence (TIRF) microscopy that FcgR3 and IFNgR locate at close vicinity to each other on the human osteoclast surface. Moreover, the averaged distance increases during the differentiation process. Interestingly, FcgR and IFNgR activation shapes the position of both receptors to each other. Surprisingly, the inhibitory action of IFNg on in vitro human osteoclast differentiation depends on the osteoclast differentiation stage. Indeed, IFNgR activation in early osteoclast precursors completely inhibits the formation of polynucleated osteoclasts while in pre-mature osteoclasts it further enhanced their fusion. In addition, gene expression analyses showed that IFNgR activation on early precursor cells but not on pre-mature osteoclasts could induce FcR expression, suggesting a co-regulation of both receptors on human osteoclast precursors. Phosphokinase array data of precursor cells demonstrate that the observed divergences of IFNgR signaling is dependent on the Mitogen‑activated protein kinase (MAPK) downstream signaling pathway. Overall, our data indicate that FcgR and IFNgR signaling pathways co-influences the differentiation and activity of osteoclasts dependent on the differentiation state, which might reflect the different stages in RA.